A Visual Presentation of Self: Photo Essays as a tool for teaching Introduction to Sociology at a Public Community College. - Buhl, Michael (TRAILS: Teaching Resources and Innovations Library for Sociology, 2023)
This assignment has been utilized in an Intro to Sociology course in an effort for students to better understand how socialization helped to shape their own self/identities. Utilizing arts-based methods, students create a PowerPoint presentation that includes their own pictures and other important resonating objects (stuffed teddy-bears etc.) from their early childhood or mid-teenage years that connects with any of the major agents of socialization (Family, School, Peers, Media, Religion etc.). A scaffolding approach was used during the early phases of introducing the assignment that included an optional worksheet provided by the instructor several weeks before the deadline period. In addition, a demo-PowerPoint Presentation was produced by the instructor (From Army-Brat to Sociologist) to help students explain their own self/identify-formation process as best as they understand process during their first few weeks taking an Intro to Sociology course. Students are also provided with a standard grading rubric that helps them to further understand core requirements of the assignment. This assignment builds on Matt Reid’s assignment, Photo (Visual) Essay of Social Problems (2016) and Laura Krull’s assignment, Group Presentation of a Social Problem (2020).